Assessing the rapidly-emerging landscape of net zero targets. (14th January 2022) - Hale, Thomas; Smith, Stephen M.; Black, Richard; Cullen, Kate; Fay, Byron; Lang, John; Mahmood, Saba
ABSTRACT: In the five years since the Paris Agreement, achieving net zero emissions has become a defining frame for climate action. We review over 4000 countries, companies, and subnational governments, which together make up the preponderance of global emissions. We find 769 of these entities have net zero targets, but only 152 meet minimum criteria for robustness, including timing, status, coverage, use of offsets, and governance. Though net zero is now widespread as a concept, its operationalization is still in its infancy. Making net zero targets robust should now be a priority for policymakers in order to deliver Paris-consistent action, as well as securing more ambitious targets. Key policy insights Net zero targets now cover two-thirds of the global economy, but robust net zero targets only cover around five percent. Strengthening targets and their implementation is particularly needed in the following areas: target status (including setting targets into law); coveraneuge of activities; limits to and transparency regarding the use of offsets; and publication of plans and of progress reports. Policymakers should aim to strengthen net zero targets by setting standards for robust net zero targets; building the capacity of entities, particularly those in the global South, to meet the technical and resource challenges required to effectively operationalize net zero emission targets.